Immunosuppressants in Liver Transplant Recipients With Coronavirus Disease 2019: Capability or Catastrophe?—A Systematic Review and Meta-Analysis - Yadav, Dipesh Kumar; Adhikari, Vishnu Prasad; Ling, Qi; Liang, Tingbo (Frontiers in medicine, 2021)
Background: The probable impact of a maintenance immunosuppressant (IS) on liver transplant (LT) recipients with coronavirus disease 2019 (COVID-19) remains unexplored. Our specific aim was to approximate the prognosis of LT recipients with COVID-19 on the standard maintenance IS. Method: We searched separate databases for the qualified studies in between December 2019 and June 25, 2021. Ultimately, a meta-analysis was carried out using a fixed-effect or random-effect model based on the heterogeneity. Results: In a total of eight studies and 509 LT recipients with COVID-19, the pooled rates of severity and mortality during all the combined immunosuppressive therapies were 22.4 and 19.5%, respectively. Our study sufficiently showed that an immunosuppressive therapy in LT recipients with COVID-19 was significantly associated with a non-severe COVID-19 [odds ratio (OR): 11.49, 95% CI: 4.17–31.65; p < 0.001] and the survival of the patients (OR: 17.64, 95% CI: 12.85–24.22; p < 0.001). Moreover, mammalian target of rapamycin inhibitor (mTORi) typically had the lowest rate of severity and mortality compared to other ISs such as calcineurin inhibitors (CNIs), steroids, and antimetabolites, i.e., severity (13.5 vs. 21.1, 24.7, and 26.3%) and mortality (8.3 vs. 15, 17.2, and 12.1%), respectively. Contrary to the general opinions, our meta-analysis showed comorbidities such as diabetes, hypertension, cardiopulmonary disorders, chronic kidney disease (CKD), age >60, the duration of LT to the diagnosis of COVID-19, primary disease for LT, and obesity were not significantly associated with the severity and mortality in LT recipients with COVID-19 under an immunosuppressive therapy. However, our pooled analysis found that LT recipients with COVID-19 and without comorbidities have a less severe disease and low mortality rate compared to those with both COVID-19 and comorbidities. Conclusions: In conclusion, LT recipients with COVID-19 undergoing immunosuppressive therapies are not significantly associated with the severity and mortality. Therefore, taking the risk of organ rejection into a key consideration, a complete withdrawal of the IS may not be wise. However, mycophenolate mofetil (MMF) might be discontinued or replaced from an immunosuppressive regimen with the CNIs- or mTORis-based immunosuppressive therapy in some selected LT recipients with COVID-19, depending upon the severity of the disease.